The ideal Muslim: Interpreting construction of new self standards in @ukhtiakhiantiselfie Instagram account - Syarifah Nur Aini; Awanis Akalili; Benni Setiawan (Universitas Negeri Yogyakarta, 2023)
Media as a medium of construing discourse, for example a dominant figure religion. In Islam the ideal muslim shown by the media that has a role as a medium for forming new ideologies in religious aspects. This research aims to explore the ideal Muslim discourse on the Instagram social media account @ukhtiakhiantiselfie. This research uses a qualitative method with content analysis in the form of Norman Fairclough's critical discourse analysis and focuses on the level of text presented in the content on the Instagram social media account @ukhtiakhiantiselfie. To find out the extent of the truth of the research, the author uses data validity techniques in the form of triangulation of data sources. Meanwhile, data analysis techniques consist of data selection, interpretation and interpretation of the text, data presentation and discussion, to draw conclusions. The results of this study indicate that the ideology constructed in the Instagram account @ukhtiakhiantiselfie is in the form of a ban on uploading photos to social media for men (muslimin) and women (muslimah). In addition, there is an ideal Muslim standard for Muslims, namely individuals who do not upload photos of themselves, achievements, possessions, and others to the public via social media. Meanwhile, the discourse that is presented refers to the ideal Muslim character according to Hamka in the form of istiqomah, namely showing firm actions towards the establishment and carrying out the commands of Allah SWT and avoiding His prohibitions. The results of this research show that the ideology constructed in the Instagram account @ukhtiakhiantiselfie is a prohibition on uploading photos to social media for men (Muslims) and women (Muslimah). Apart from that, there is an ideal Muslim standard for Muslims, namely individuals who do not upload photos of themselves, their achievements, possessions and so on to the public via social media. Meanwhile, the discourse presented refers to the ideal Muslim characteristic according to Hamka in the form of istiqomah, namely showing firm actions towards standing and carrying out the commands of Allah SWT and staying away from His prohibitions. The results of this research show that the ideology constructed in the Instagram account @ukhtiakhiantiselfie is a prohibition on uploading photos to social media for men (Muslims) and women (Muslimah). Apart from that, there is an ideal Muslim standard for Muslims, namely individuals who do not upload photos of themselves, their achievements, possessions and so on to the public via social media. Meanwhile, the discourse presented refers to the ideal Muslim characteristic according to Hamka in the form of istiqomah, namely showing firm actions towards standing and carrying out the commands of Allah SWT and staying away from His prohibitions.